First feedback during series fabrication of ITER like divertor tungsten components for the WEST tokamak. (4th October 2021) - Firdaouss, M; Li, Q; Lipa, M; Luo, G; Missirlian, M; Richou, M; Wang, W
Abstract: Purpose of WEST is to test key technologies for future device like ITER. In particular the actively cooled plasma facing component technology, the so-called tungsten monoblock, will equip the lower divertor, allowing studies and analyses of the plasma wall interaction. 456 plasma-facing components have been manufactured during the last years, using hot isostatic pressing as main bonding process. The manufacturing of the components was not completely straightforward; however, it was successful and main requirements have been reached. The key manufacturing steps, as well as the associated controls are described.